Effect of Fertilizer Faeces On Parameter of Physical Chemistry in Peat Swamp Soil In The Media - Pamungkas, Rhino; Hasibuan, Saberina; ', Syafriadiman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research was conducted from March 2014 in the Laboratory Management ofWater Quality, Faculty of Fisheries and Marine Sciences University of Riau Pekanbaru.The method used in this study is an experimental method using a Random Block Design(RAL) with one factor, 5 treatments and 3 replications. The treatment used in thisexperiment is P0: Without application of fertilizer faeces (control), P1: faeces fertilizer300g/m2, P2: faeces fertilizer 450g/m2, P3: faeces fertilizer 600g/m2, P4: faeces fertilizer750g/m2. Result showed that the faeces fertilizer amounts affect various physical andchemical water quality and well as soil chemistry of peat, and may increase some of thephysical parameter of water quality and soil chemistry of peat swamp and fainally togood fertility for the growth of organisms in the water.Keyword : Fertilizer faeces, chemistry and physical parameter, water and soil quality